Book review: Wladimir Köppen – Scholar for Life; Wladimir Köppen – ein Gelehrtenleben für die Meteorologie: Else Wegener-Köppen, Jörn Thiede (Eds.). Stuttgart 2018 - Eugster, Werner (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
No abstract necessary